Analysis of risk factors contributing to neonatal pneumonia in low birth weight neonates - Xu, Xiaoli; Deng, Yongmin; Han, Jingjing; Wang, Jing; Huang, Rui; Zhao, Xiaoyan (Frontiers in Pediatrics, 2025)
ObjectiveThe current study aims to investigate the high-risk determinants associated with the occurrence of pneumonia in low birth weight (LBW) neonates.MethodsA retrospective case-control study was conducted at The First Hospital of Hebei Medical University, a tertiary care center in Shijiazhuang, China, for neonates born between January 2019 and December 2023. From a cohort of 230 LBW neonates admitted to the NICU, 90 neonates diagnosed with pneumonia were designated as the observation group, while 50 LBW neonates without pneumonia were selected as the control group. Statistical hypothesis testing was employed for data analysis, including univariate and multivariable logistic regression analyses.ResultsUnivariate analysis identified several significant risk factors for neonatal pneumonia, including low birth weight, prematurity (gestational age <37 weeks), small-for-gestational-age (SGA) status, neonatal anemia, patent ductus arteriosus, neonatal hyperbilirubinemia, maternal hypothyroidism during pregnancy, and prenatal infection (P < 0.05). Multivariable logistic regression analysis that included all significant univariate predictors revealed that birth weight (OR for <1,600 g vs. ≥2,200 g = 7.112, 95% CI: 1.650–30.651) and small-for-gestational-age status (OR = 2.598, 95% CI: 1.152–5.859) remained as the sole independent risk factors for neonatal pneumonia in LBW neonates.ConclusionBirth weight and small-for-gestational-age status are independent risk factors for neonatal pneumonia in low birth weight neonates. SGA neonates born at very early gestational ages (<32 weeks) represent a particularly high-risk subgroup.